The correlation calibration of PAPER-64 data. Issue 2 (3rd December 2021) - Gogo, Tamirat G; Ma, Yin-Zhe; Kittiwisit, Piyanat; Sievers, Jonathan L; Parsons, Aaron R; Pober, Jonathan C; Jacobs, Daniel C; Cheng, Carina; Kolopanis, Matthew; Liu, Adrian; Kohn, Saul A; Aguirre, James E; et al.
ABSTRACT: Observation of redshifted 21-cm signal from the Epoch of Reionization (EoR) is challenging due to contamination from the bright foreground sources that exceed the signal by several orders of magnitude. Removal of this very high foreground relies on accurate calibration to keep the intrinsic property of the foreground with frequency. Commonly employed calibration techniques for these experiments are the sky model-based and the redundant baseline-based calibration approaches, which can suffer from sky-modelling error and array redundancy imperfection respectively. In this work, we introduce the hybrid correlation calibration (CorrCal ) scheme, which aims to bridge the gap between redundant and sky-based calibration by relaxing redundancy of the array and including sky information into the calibration formalisms. We apply the CorrCal to the data of Precision Array for Probing the Epoch of Reionization (PAPER) experiment, which was pre-calibrated using redundant baseline calibration. We show about 6% suppression at the bin right on the horizon limit of the foreground wedge-like structure, relative to the pre-calibrated power spectra. This small improvement of the foreground power spectra around the wedge limit could be suggestive of reduced spectral structure in the data after CorrCal calibration, which lays the foundation for future improvement of the calibration algorithm and implementation method.